2021
DOI: 10.3390/rs14010045
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Segmentation and Analysis on Sensitive Parameters of Forest Fire Smoke Using Smoke-Unet and Landsat-8 Imagery

Abstract: Forest fire is a ubiquitous disaster which has a long-term impact on the local climate as well as the ecological balance and fire products based on remote sensing satellite data have developed rapidly. However, the early forest fire smoke in remote sensing images is small in area and easily confused by clouds and fog, which makes it difficult to be identified. Too many redundant frequency bands and remote sensing index for remote sensing satellite data will have an interference on wildfire smoke detection, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 43 publications
1
38
0
3
Order By: Relevance
“…It is one of our fundamental research questions in this paper to address the need for using VIs as hand-crafted features, instead of end-to-end training. In [109], it has already been shown that adding the input of extra-bands causes an inference to the network parameter learning and this, in turn, causes a degradation of the network performance. We believe that even if the input of all band data can increase the global information, those extra bands may be insufficient to identify detailed small tree objects in the scene [110].…”
Section: B Resultsmentioning
confidence: 99%
“…It is one of our fundamental research questions in this paper to address the need for using VIs as hand-crafted features, instead of end-to-end training. In [109], it has already been shown that adding the input of extra-bands causes an inference to the network parameter learning and this, in turn, causes a degradation of the network performance. We believe that even if the input of all band data can increase the global information, those extra bands may be insufficient to identify detailed small tree objects in the scene [110].…”
Section: B Resultsmentioning
confidence: 99%
“…Data obtained from different platforms can provide diverse and complementary information [46]- [47]. The smoke datasets for optical satellite images mostly come from lowresolution multi-spectral images such as MODIS [48], Himawari-8 [49], LandSat-8 [50], and GOES-16 [51]. The lack of large-scale, open-source, high-resolution labeled datasets for segmentation restricts the development of smoke segmentation network models for high-resolution optical satellite imagery.…”
Section: B Deep-learning-based Smoke Segmentation Methodsmentioning
confidence: 99%
“…As a result of experiments, they achieved 82.2% IoU value and 90% accuracy for building segmentation. Wang et al [12] worked on removing the difficulties in early forest fire detection through satellite images. They stated that early forest fires could be mis-detected as clouds.…”
Section: Literature Reviewmentioning
confidence: 99%